Assessing the Effect of Middle Ear Effusions on Wideband Acoustic Immittance Using Optical Coherence Tomography - Won, Jungeun (Ear Hear, 2019)
Wideband acoustic immittance (WAI) noninvasively assesses middle ear function by measuring the sound conduction over a range of audible frequencies. Although several studies have shown the potential of WAI for detecting the presence of middle ear effusions (MEEs), determining the effects of MEE type and amount on WAI in vivo has been challenging due to the anatomical location of middle ear cavity. The purpose of this study is to correlate WAI measurements with physical characteristics of the middle ear and MEEs determined by optical coherence tomography (OCT), a noninvasive optical imaging technique. DESIGN: Sixteen pediatric subjects (average age of 7 ± 4 years) were recruited from the primary care clinic at Carle Foundation Hospital (Urbana, IL). A total of 22 ears (normal: 15 ears, otitis media with effusion: 6 ears, and acute otitis media: 1 ear, based on physician’s diagnosis) were examined via standard otoscopy, tympanometry, OCT imaging, and WAI measurements in a busy, community-based clinical setting. Cross-sectional OCT images were analyzed to quantitatively assess the presence, type (relative turbidity based on the amount of scattering), and amount (relative fluid level) of MEEs. These OCT metrics were utilized to categorize subject ears into no MEE (control), biofilm without a MEE, serous-scant, serous-severe, mucoid-scant, and mucoid-severe MEE groups. The absorbance levels in each group were statistically evaluated at α = 0.05. RESULTS: The absorbance of the control group showed a similar trend when compared with a pediatric normative dataset, and the presence of an MEE generally decreased the power absorbance. The mucoid MEE group showed significantly less power absorbance from 2.74 to 4.73 kHz (p < 0.05) when compared with the serous MEE group, possibly due to the greater mass impeding the middle ear system. Similarly, the greater amount of middle ear fluid contributed to the lower power absorbance from 1.92 to 2.37 kHz (p< 0.05), when compared with smaller amounts of fluid. As expected, the MEEs with scant fluid only significantly affected the power absorbance at frequencies greater than 4.85 kHz. A large variance in the power absorbance was observed between 2 and 5 kHz, suggesting the dependence on both the type and amount of MEE. CONCLUSIONS: Physical characteristics of the middle ear and MEEs quantified from noninvasive OCT images can be helpful to understand abnormal WAI measurements. Mucoid MEEs decrease the power absorbance more than serous MEEs, and the greater amounts of MEE decreases the power absorbance, especially at higher (>2 kHz) frequencies. As both the type and amount of MEE can significantly affect WAI measurements, further investigations to correlate acoustic measurements with physical characteristics of middle ear conditions in vivo is needed.